P.S. I still love you - Han, Jenny (Simon & Schuster BFYR, 2015)
"Lara Jean didn't expect to really fall for Peter. She andPeter were just pretending. Except suddenly they weren't. Now Lara Jean is more confused than ever. When another boy from her past returns to her life, Lara Jean's feelings for him return too. Can a girl be in love with two boys at once?"